36th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2000
DOI: 10.2514/6.2000-3790
|View full text |Cite
|
Sign up to set email alerts
|

Variable density multilayer insulation for cryogenic storage

Abstract: Two analytical models for a foam/Variable Density Multi-Layer Insulation (VD-MLI) system performance are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Recently, the concept of variable density MLI (VD-MLI), where two distinct layers of MLI with a different layer density are combined, has been introduced [52,53,61e63] and it has been shown that the lowest possible foil spacing at the hottest boundary results in the best design [62,63]. Compared to the classical single density MLI configuration, VD-MLI can lead to a boil-off reduction of 58%, or a weight saving of 41% for the same boil-off amount [52,53]. To minimize the heat leakage into the tank, another insulation technique has been used by combining MLI and a vapor-cooled shield (VCS) [64,65].…”
Section: Insulation Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of variable density MLI (VD-MLI), where two distinct layers of MLI with a different layer density are combined, has been introduced [52,53,61e63] and it has been shown that the lowest possible foil spacing at the hottest boundary results in the best design [62,63]. Compared to the classical single density MLI configuration, VD-MLI can lead to a boil-off reduction of 58%, or a weight saving of 41% for the same boil-off amount [52,53]. To minimize the heat leakage into the tank, another insulation technique has been used by combining MLI and a vapor-cooled shield (VCS) [64,65].…”
Section: Insulation Materialsmentioning
confidence: 99%
“…However, for a given installation method, the choice of radiative blanket and spacer material also has a considerable influence on the thermal performance of the MLI. The thin radiation shields are usually made of plastic film (Mylar or Kapton) coated on one or both sides with a thin layer of high reflectance metal, such as aluminium or gold (thickness of about 500 Å [50,52,53]), while polyester, glass fiber paper, nylon netting or silk tissue is often used for the spacer material [50,53e55]. The combination of spacers and screens minimizes the main modes of heat transfer, i.e.…”
Section: Insulation Materialsmentioning
confidence: 99%
“…Furthermore, a large number of radiation shield means increase of material and assembly costs in the experiment. It follows that the layer density must be optimized [18,32]. This optimization can be performed by varying the distance between layers and adjusting the number of layers within a fixed thickness of the insulation blanket.…”
Section: Optimization Of the Layer Density In MLI Techniquementioning
confidence: 99%
“…Such MLI systems are used in storage of high value cryogens and thus tend to be custom made in small quantities without concern for repeatability and mass production in an industrial environment. Nevertheless, the studies show significant benefit of using variable density insulation [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of literature available on variable density MLI is limited [1,4,6], however there is increasing interest in using it in space vehicle support systems [2,3,7]. Such MLI systems are used in storage of high value cryogens and thus tend to be custom made in small quantities without concern for repeatability and mass production in an industrial environment.…”
Section: Introductionmentioning
confidence: 99%